Infection by invasive parasites increases susceptibility of native hosts to secondary infection via modulation of cellular immunity. Issue 3 (17th January 2019) - Demann, Felicitas; Wegner, K. Mathias
Abstract: Parasite spillover from invasive aliens to native species increases the risk of disease emergence within native biota—either by direct harm to the new host or by indirect effects like increased risks of secondary infection. One example for such a detrimental effect is the parasitic copepod Mytilicola intestinalis that infected blue mussels Mytilus edulis after being introduced into the North Sea in the early 20th century. Since 1949, the parasite was blamed for multiple mass mortalities of infested blue mussels but evidence for a direct causal involvement of M. intestinalis remained circumstantial. Here, we now examine the potential effects of primary infections by the invasive parasite on the susceptibility to secondary infections with virulent bacteria ( Vibrio spp.) in a full factorial infection experiment combining parasite infection (control vs. infected) with different Vibrio infection treatments (control, bath challenge, injection) in environmental conditions that either favoured the host (ambient temperature) or the bacterium (elevated temperature). The influence of primary and secondary infections on cellular immunity (phagocytosis) and Vibrio load in the haemolymph was used to correlate these results to host survival. Our results suggest that the rate of secondary Vibrio infection is increased due to lower efficiency of the cellular immune response. As a consequence, the failure of clearing Vibrio from the haemolymph might increase mortality of mussels infected by M. intestinalis . This demonstrates that indirect effects of parasite invasions can outweigh direct effects of the infection highlighting the need for a more integrative approach to understand and predict the consequences of parasite invasions. Abstract : This paper demonstrates that indirect effects of immune modulation caused by infection with an invasive parasite can outweigh direct effects of the infection. This highlights the need for a more integrative approach to predict the consequences of parasite invasions and species invasions in general.